Pooled analysis of 3 European case-control studies of ovarian cancer: II. Age at menarche and at menopause. - Franceschi, S; La Vecchia, C; Booth, M; Tzonou, A; Negri, E; Parazzini, F; Trichopoulos, D; Beral, V (1991)
The role of age at menarche and at menopause on epithelial ovarian cancer risk was re-assessed in a combined analysis of 3 hospital-based case-control studies conducted in Italy, the United Kingdom and Greece, which produced a total of 1,140 cases and 2,724 controls. In the overall dataset, there was no evidence of an association with age at menarche: compared with women whose menarche occurred at age 15 or over, the relative risk (RR) estimates were 1.0 [95% confidence interval (CI) 0.8 to 1.2] for those with menarche at ages 12 to 14, and 1.0 (95% CI 0.8-1.2) for those with menarche below age 12. There was no consistent interaction between age at menarche and study centre or age at diagnosis. In relation to age at menopause, compared with women whose menopause occurred at age 44 or earlier, the RR was 1.4 between 45 and 49, 1.6 between 50 and 52 and 1.9 above 52. The strength of the association was apparently (but not significantly) greater in the British than in the Greek or Italian dataset. The effect of age at menopause tended to be long-lasting and, if anything, to increase across subsequent age-groups. The large dataset, and the replication of results in different studies, provide more definite and precise information than previously available on the absence of appreciable effect of age at menarche on subsequent ovarian cancer risk in developed countries. For age at menopause, there was a direct and consistent trend in risk, but the association was relatively weak, with RRs below 2 even between extreme categories.